[Spichlerz Królewski] - Nowaliński, Karol (1935- ). ([Gdańsk : Karol Nowaliński, 1986)
Przedstawia Spichlerz Królewski na Ołowiance, widok od płd.-zach., ok. 1910 r.
Aut. odb. data i miejsce wyd. wg inwentarza PAN BG.
Fot. Gd.